2008
DOI: 10.1021/jp809329a
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Characterization of a Stable Tryptophan Radical in an Azurin Mutant

Abstract: Tryptophan radicals play a significant role in mediating biological electron transfer and catalytic processes. Here, we employ visible and UV resonance Raman, EPR, and absorption spectroscopy along with pH/isotope studies and calculations to probe a neutral closed-shell tryptophan and its oxidized radical counterpart in a modified azurin protein. Comparison of the resonance Raman spectra of the radical and closed-shell species combined with vibrational analysis reveals important structural differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 72 publications
8
59
0
Order By: Relevance
“…57 The W17 Raman shift for the closed shell Trp UV resonance Raman spectrum (230 nm excitation) of radical forming Az108W is 880 cm −1 , shifting to 875 cm −1 in the neutral radical. 58 A W17 Raman shift of 878 cm −1 (229 nm excitation) has been reported for the closed shell His37-Trp41 cation-π interaction at pH 4 in the M2 ion channel of the influenza A virus, 59 and was also attributed to hydrogen bonding with water. Involvement in a strong hydrogen bond at the indole amine for the Trp neutral radical has been predicted 48,49 and is supported by the 5 cm −1 downshift in the W17 Raman frequency reported for Az108W upon radical formation.…”
Section: Resultsmentioning
confidence: 92%
“…57 The W17 Raman shift for the closed shell Trp UV resonance Raman spectrum (230 nm excitation) of radical forming Az108W is 880 cm −1 , shifting to 875 cm −1 in the neutral radical. 58 A W17 Raman shift of 878 cm −1 (229 nm excitation) has been reported for the closed shell His37-Trp41 cation-π interaction at pH 4 in the M2 ion channel of the influenza A virus, 59 and was also attributed to hydrogen bonding with water. Involvement in a strong hydrogen bond at the indole amine for the Trp neutral radical has been predicted 48,49 and is supported by the 5 cm −1 downshift in the W17 Raman frequency reported for Az108W upon radical formation.…”
Section: Resultsmentioning
confidence: 92%
“…21 The majority of peaks are downshifted in Az48W • relative to solvent-exposed ReAz108W • , with the exception of W7 • , W16 • , and W19 • modes. On the basis of mode assignments and RR frequency differences between the radical and the closed-shell Trp species as well as between the buried and the solvent-exposed Trp • , Shafaat et al 21,32 have identified modes that are most sensitive to solvent, protein environment,and/or hydrogen-bonding changes. These include W1 • , W5 • , W12 • , W13 • , and W17 • modes.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, optical and vibrational spectroscopies, especially resonance Raman (RR) spectroscopies, have been rarely employed to study these species. 30,31 The recent photogeneration of a long-lived Trp • in two Pseudomonas aeruginosa azurin mutants, [Y72F/Y108F]AzCu-(II) (Az48W) and the rhenium-labeled Az108W mutant [Re(I)(CO) 3 (4,7-dimethyl-1,10-phenanthroline)(Q107H)]-(W48F/Y72F/H83Q/Y108W)AzM(II) [M = Cu, Zn] (ReAz108W), provided the unique opportunity to obtain the electronic, magnetic, and vibrational spectra of these radical species 21,22,32 and identify the spectral signatures of Trp radicals that are sensitive to the local environment. Indeed, in Az48W the radical (W48 • ) is buried in the hydrophobic core (see Figure 1, left), while it is solvent-exposed (W108 • ) in ReAz108W (see Figure 1, right).…”
Section: Introductionmentioning
confidence: 99%
“…28 The surprising stability of this neutral tryptophan radical in azurin allowed us and others to characterize its absorption, resonance Raman, and EPR spectra, and to compare these spectra to another stable tryptophan radical generated at position 108. 2730 In these prior reports, the mechanism of formation of W48• was hypothesized to be an intramolecular process. Here, we present evidence that both intra- and intermolecular charge transfer events take place.…”
Section: Introductionmentioning
confidence: 99%